Physical, optical and luminescence properties of the Dy3+doped barium borophosphate glasses - Sujita Karki (2019)
© 2019 Elsevier B.V. Barium borophosphate glasses doped with dysprosium oxide had been fabricated by conventional melt quenching technique using the chemical composition of: (25BaO: 5B2O3: 70-xP2O5: xDy2O3)), where (x = 0.2, 0.4, 0.6, 0.8 and 1.0, mol%) (BaBPDy). The physical, optical and luminescence properties are studied for possibility of using as a white luminescence materials for solid-state light emitting devices. Judd-Ofelt (JO) theory is applied to study the radiative properties of the luminescence level of Dy3+ ions. The effect of the concentration quenching due to increase in Dy3+ ions is discussed in details. The lifetime of all BaBPDy concentration glass is bi-exponential in nature, which is discussed in the present work. This non-exponential nature of the decay curve was fitted by using the well-known Inokuti-Hirayama (IH) model S= 6, indicating that the energy transfer process is dipole-dipole type. The chromaticity co-ordinate(x, y) is evaluated from the luminescence spectra and its possibility for using as a white light application has been analyzed.